Electrochemical Method Development for Enalapril Determination in a Pharmaceutical Formulation - Amro, Abdulaziz (Asian Journal of Pharmaceutics (AJP), 2020)
Aims: The present study focuses on a comparison between three voltammetric methods for enalapril assay in a pharmaceutical formulation, in addition to optimization of voltammetric analysis parameters such as working electrode and supporting electrolyte. Materials and Methods: Glassy carbon (GC) working electrode and KNO3 (1 M) supporting electrolyte exhibited the best performance compared to other working electrodes and supporting electrolytes used in this study. Results and Discussion: Voltammograms of enalapril exhibited two oxidization peaks at 1.4 V and 1.75 V. Square wave voltammetry (SWV) showed the lowest limit of detection (LOD) and limit of quantitation (LOQ) with values of 90.1 and 247 Î¼g/mL LOD and LOQ, respectively. Furthermore, SWV exhibited the lowest relative standard deviation values of 2.33 and 3.87% for inter and intraday analysis, respectively. SWV showed high-performance in recovery study of commercially available enalapril tablets ANGIOTEC 20 mgÂ® reach 99.06%. Conclusion: Accuracy, precession, and detection limit of SWV are the best for enalapril analysis compared to other methods in this study.